Parametric study of varying ribs orientation and sweep angle of un-tapered wing box model - Nee Chan, Ying; Yazdi Harmin, Mohammad; Safuan Othman, Mohd (International Journal of Engineering and Technology, 2018)
A simple un-tapered wing box model was considered to illustrate an aeroelastic tailoring of varying ribs orientation with respect to a range of sweep angles. This approach allows the bending-torsional modes characteristic to be altered hence offering possibility for improvement in aeroelastic performance without having to compromise its overall weight. Two cases of ribs orientation were considered for a range of sweep angles. The first case was by allowing one individual ribs to be orientated at a time and the second case considering all possible combination of ribs orientation. The finding shows that the torsional modes are greatly influenced by the rib orientation while the bending modes are not significantly affected. Therefore, this enable the frequency gap between the flutter modes to be altered; hence resulting into significant impact to aeroelastic performances. It has been found that for all the considered sweep angles, the varying ribs orientation can lead into an improvement of nearly 80-90% when compared to its corresponding baseline configuration. Therefore, this provides a leverage for an advancement in aeroelastic performance without having to penalize the total weight of the wing structure.Â Â